Sex related haematological variations in Himalayan golden mahseer, Torputitora (Ham.) - Kapila, R; Kapila, S; Basade, Y (Indian Journal of Fisheries, 2011)
With a view to monitor the health status of the endangered golden mahseer for effective conservation measures, the haematological investigations were carried out on blood collected from the heart of ripe specimens netted out from Bhimtal lake during spawning season. The sex related studies indicated that the males had statistically significant (p<0.05) higher values of specific gravity, red blood cells (RBC), haemoglobin (Hb), packed cell volume (PCV) as compared to their female counterparts, while females were observed to have remarkably (p<0.01) higher values of white blood cells (WBC). On the other hand, nonsignificant variations were noticed in mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), mean corpscular volume (MCV) and serum protein levels between the two sexes.